2017
DOI: 10.1111/liv.13642
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐mediated suppression of IL‐37 licenses alcoholic liver disease

Abstract: We provide evidence for an exogenous noxae that suppresses Interleukin 37 expression which limits its anti-inflammatory effects in alcoholic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…8- to 10-week-old female wild-type (C57BL/6) mice were fed with a Lieber-DeCarli diet containing up to 5% alcohol for 15 days (EtOH-fed) or Lieber-DeCarli diet alone (pair-fed), as shown in Figure 1a and previously described. 33 , 53 …”
Section: Methodsmentioning
confidence: 99%
“…8- to 10-week-old female wild-type (C57BL/6) mice were fed with a Lieber-DeCarli diet containing up to 5% alcohol for 15 days (EtOH-fed) or Lieber-DeCarli diet alone (pair-fed), as shown in Figure 1a and previously described. 33 , 53 …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, IL-37 has been associated with anti-inflammatory effects via IL-18Rα and IL-1R8 expression. In liver samples of ASH subjects, IL-37 expression was substantially reduced when compared to non-alcoholic fatty liver disease subjects [45] . An in vivo system in wild-type mice suggested that hepatic IL-37 expression was suppressed by ethanol through the administration of human recombinant IL-37 followed by oral gavage of an ethanol shot in those animals [45] .…”
Section: Mechanisms Involved In Hcc Developmentmentioning
confidence: 86%
“…In liver samples of ASH subjects, IL-37 expression was substantially reduced when compared to non-alcoholic fatty liver disease subjects [45] . An in vivo system in wild-type mice suggested that hepatic IL-37 expression was suppressed by ethanol through the administration of human recombinant IL-37 followed by oral gavage of an ethanol shot in those animals [45] . This is important since HCC clinical specimens have shown that decreased expression of IL-37 is negatively correlated with tumor size and positively associated with better overall survival and disease-free survival via the induction of tumor-infiltrating CD571 natural killer cells [46] .…”
Section: Mechanisms Involved In Hcc Developmentmentioning
confidence: 86%
“…Consistent with the murine results, patients with alcoholic steatohepatitis showed decreased expression of IL-37 in the liver compared to NAFLD patients. 195 In chronic liver diseases, such as ASH and NASH, fibrosis is characterized by the deposition of extracellular matrix (ECM), which contributes to organ failure. Gieling et al highlighted the role of IL-1 in the activation of HSCs, enabling the transition from liver injury to fibrosis.…”
Section: Il-1 Family Cytokinesmentioning
confidence: 99%